(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
Social media platforms have become important channels through which prospective students obtain information, interact with institutions, and develop perceptions about educational opportunities. Despite the growing use of social media marketing by higher education institutions, there is limited evidence on how different dimensions of social media marketing influence students’ enrolment decisions in developing countries such as Nepal. Guided by the Theory of Planned Behaviour, this study examines the influence of social media accessibility, content quality, engagement, brand awareness, and paid advertising on students’ enrolment decisions in Nepalese Higher Management Educational Institutions. This research used a convergent parallel mixed-methods design, with quantitative data collected from a survey of two hundred and thirty-nine (N=239) bachelor-level management students and qualitative data from interviews with nine participants. Quantitative data were analysed using descriptive statistics, principal component analysis, independent-samples t-tests, and binary logistic regression. Qualitative data were analysed using thematic analysis. The results show that parental social media activity, engagement in digital communities for prospective students, and clarity of social media content are the main factors affecting enrolment decisions. Conversely, peer influence, information accessibility, and paid advertisements had a small direct effect on enrolment outcomes. The study contributes to the Theory of Planned Behaviour by integrating cultural and family influences in a developing country context and emphasising the importance of family involvement and credible digital communication in higher education marketing, which have practical implications for educational institutions seeking to improve recruitment success through targeted, culturally appropriate social media approaches.